Investigation of antioxidant and antimicrobial activity of zingiber officinale roscoe oleosin on airborne pathogenic microorganisms - Sharif, Mohd Faez; Zahaba, Maryam; Ariffin, Nur Ariffadilla; Mohd Ghazi, Zati Nabilah; Mohd Aris, Mohd Shukri (Universiti Teknologi Mara (UiTM) Pulau Pinang, 2017)
Zingiber Officinale Roscoe or ginger has been found to have characteristics that are beneficial to human beings for different purposes. In this study, oleoresins from both young and mature gingers were studied to evaluate their antioxidant and antimicrobial activity on common airborne pathogenic microorganisms. The total phenolic and antioxidant contents were tested using the Folin–Ciocalteu method and DPPH (2, 2-diphenyl-1- picrylhydrazyl) scavenging activity assay respectively. Meanwhile, antimicrobial activity was determined using the disc diffusion and minimum inhibitory concentration (MIC) against two pathogenic bacteria and fungi; namely S. aureus, P. aeruginosa, C. albicans, and A. niger. Young ginger oleoresin exhibits higher total phenolic contents (129.5869 ± 14.27 GAE) and antioxidant activity (99.06 % ± 1.41) than matured ginger oleoresin. In the antimicrobial study, the result showed that both young and matured oleoresins were able to inhibit the growth of common airborne pathogenic bacteria. However, common airborne pathogenic fungi were resistant to both oleoresin of ginger extract. The oleoresin was able to suppress the growth of S. aureus at the low concentration of 1 mg/ml rather than P. aeruginosa at 10 mg/ml. Young ginger possess higher antioxidant and antibacterial activity than matured ginger.